Modified sodium ion battery positive electrode material, preparation method thereof and sodium ion battery

By forming a cladding layer with concentration gradient and a metal oxide shell on the layered oxide positive electrode material of the sodium ion battery, the problems of structural collapse and capacity decay during the circulation process are solved, and the battery performance and cost reduction are achieved.

CN119674037APending Publication Date: 2025-03-21HUNAN MEITE XINCAILIAO SCI & TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411945958.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The sodium ion layered oxide positive electrode material has an irreversible phase change during the cycle, resulting in structural collapse and capacity attenuation, and the high cost of synthesis of precursors, limiting its development in sodium ion batteries.

Method used

The modified sodium ion battery positive electrode material is adopted, including the layered oxide positive electrode material of O3 type sodium ion battery, the cladding layer is a NayMxN1-x(SiO4)2(PO4) layer with a concentration gradient, and a further metal oxide cladding layer, and a gradient structure and a shell are formed by multiple sintering.

Benefits of technology

The discharge specific capacity of the battery, the first Coulomb efficiency and cycling performance are significantly improved, the cost of the material is reduced, and the electrochemical cycle stability is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119674037A_ABST
    Figure CN119674037A_ABST
Patent Text Reader

Abstract

The invention provides a modified sodium-ion battery positive electrode material and a preparation method and application thereof.The modified sodium-ion battery positive electrode material comprises an inner core and a first coating layer coating at least part of the surface of the inner core, the inner core is a sodium-ion battery layered oxide positive electrode material, the first coating layer is NayMxN1-x (SiO4) 2 (PO4), M is one or more of Ti, Al, La and Nb, and the first coating layer is NayMxN1-x (SiO4) 2 (PO4). N is one or more of Zr, Sc and Y; in the first coating layer, the concentration gradient of the M element content is increased from inside to outside, and the concentration gradient of the N element content is reduced from inside to outside. A battery assembled by the modified sodium-ion battery positive electrode material provided by the invention has obviously improved specific discharge capacity, initial coulombic efficiency and cycle performance, and can be widely applied to the energy storage market.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of sodium ion batteries, and in particular relates to the modification of layered oxide positive electrode materials of sodium ion batteries. Background Art

[0002] The widespread use of lithium-ion batteries has significantly improved people's living standards, but there are also safety hazards, such as mobile phone explosions and car spontaneous combustion, as well as the uneven distribution and high price of lithium ore resources, which further restrict the development of lithium-ion batteries. Sodium-ion batteries have similar structures and working principles to lithium-ion batteries, and sodium resources are abundant and cheap. Sodium-ion batteries have a wide operating temperature range and good safety performance, and are considered to be the next generation of battery products to replace lithium-ion batteries.

[0003] The performance of the positive electrode material directly determines the quality of the sodium-ion battery. The sodium-ion layered oxide positive electrode material has commercial prospects due to its simple preparation process and relatively high specific capacity. However, during the cycle process, some irreversible phase changes will occur in the sodium-ion layered oxide positive electrode material, causing the structure to collapse rapidly, accelerating the capacity decay. At present, most layered oxide sodium battery positive electrode materials are synthesized using precursors, and the raw material cost is high. The low capacity retention rate and high cost of sodium-ion layered oxide positive electrode materials restrict their development in sodium-ion batteries.

[0004] Therefore, improving the cycle performance and reducing the cost of sodium ion layered oxide positive electrode materials are conducive to promoting industrial development. A new type of sodium ion layered oxide positive electrode material and its preparation method are urgently needed to solve this problem. Summary of the invention

[0005] In response to the above technical problems, the present application provides a modified sodium ion battery positive electrode material and a preparation method thereof, and a sodium ion battery.

[0006] To achieve the above objectives, this application proposes the following technical solutions: In a first aspect, a modified sodium ion battery positive electrode material is provided, comprising a core and a first coating layer coated on at least a portion of the surface of the core, wherein the core is a sodium ion battery layered oxide positive electrode material, and the first coating layer is Na y M x N 1-x (SiO4)2(PO4), wherein M is one or more of Ti, Al, La, and Nb, N is one or more of Zr, Sc, and Y, x is 0.1 to 0.9, and y is 2.5 to 3.5; in the first coating layer, in the direction from the inner core to the surface, the concentration gradient of the M element content increases, and the concentration gradient of the N element content decreases.

[0007] Furthermore, the layered oxide positive electrode material for sodium ion battery is an O3 type sodium ion battery positive electrode material; the chemical formula of the O3 type sodium ion battery positive electrode material is Na a Ni b Fe c Mn d A e O2, wherein A is one or more of Ca, Mg, Ti, Al, La, Nb, and Zr, a is 0.96 to 1.05, b is 0.33 to 0.4, c is 0.295 to 0.33, d is 0.295 to 0.33, e is 0 to 0.02, and b+c+d+e=1; Furthermore, in the modified sodium ion battery positive electrode material, the Na y M x N 1-x (SiO4)2(PO4) accounts for 1~2% of the molar amount of layered oxide positive electrode materials for sodium ion batteries.

[0008] Furthermore, in the direction from the core to the surface, the first coating layer includes a first layer, a second layer and a third layer in sequence, and the first layer is Na y1 M x1 N 1-x1 (SiO4)2(PO4), the second layer is Na y2 M x2 N 1-x2 (SiO4)2(PO4), the third layer is Na y3 M x3 N 1-x3 (SiO4)2(PO4), where the value of x1 is 0.1~0.2, the value of y1 is 2.5~3.5, the value of x2 is 0.4~0.5, the value of y2 is 2.5~3.5, the value of x3 is 0.7~0.9, and the value of y3 is 2.5~3.5.

[0009] Furthermore, in the first coating layer, the molar weight of the first layer accounts for 20-35%, the molar weight of the second layer accounts for 30-40%, and the molar weight of the third layer accounts for 20-35%.

[0010] Furthermore, it also includes a second coating layer, the raw material of the second coating layer is metal oxide, and the second coating layer is coated on at least a part of the surface of the first coating layer.

[0011] Furthermore, the metal oxide is one or more of TiO2, Al2O3, ZrO2, MgO, CaO, ZnO, La2O3, Sc2O3, Y2O3, and Nb2O5.

[0012] Furthermore, the metal oxide is 0.05 to 0.15 of the molar weight of the layered oxide positive electrode material of the sodium ion battery.

[0013] In a second aspect, a method for preparing the aforementioned modified sodium ion battery positive electrode material is provided, comprising: S1, mixing a sodium ion battery layered oxide positive electrode material with a sodium source, an M source, a N source, a silicon source and a phosphorus source, and performing a first sintering to obtain an intermediate 1; S2, mixing the intermediate 1 with a sodium source, an M source, a N source, a silicon source and a phosphorus source, and performing a second sintering to obtain an intermediate 2; S3, mixing intermediate 2 with a sodium source, an M source, a N source, a silicon source and a phosphorus source, and performing a third sintering to obtain Na y M x N 1-x The first modified sodium ion battery layered oxide positive electrode material is a (SiO4)2(PO4) coated modified sodium ion battery layered oxide positive electrode material; wherein M is one or more of Ti, Al, La, and Nb, N is one or more of Zr, Sc, and Y, x is 0.1 to 0.9, y is 2.5 to 3.5, and in the first modified sodium ion battery layered oxide positive electrode material, in the direction from the inner core to the surface, the concentration gradient of the M element content increases, and the N element content decreases from the concentration gradient.

[0014] Further, in step S1, the M source, N source, silicon source and phosphorus source are prepared according to Na y1 M x1 N 1-x1 (SiO4)2(PO4) ratio; In step S2, the M source, N source, silicon source and phosphorus source are in the order of Na y2 M x2 N 1-x2 (SiO4)2(PO4) ratio; in step S3, the M source, N source, silicon source and phosphorus source are in accordance with Na y3 M x3 N 1-x3 (SiO4)2(PO4) ratio; the value of x1 is 0.1~0.2, the value of y1 is 2.5~3.5, the value of x2 is 0.4~0.5, the value of y2 is 2.5~3.5, the value of x3 is 0.7~0.9, and the value of y3 is 2.5~3.5.

[0015] Furthermore, the sodium source is one or more of sodium carbonate, sodium hydroxide and sodium acetate.

[0016] Further, the phosphorus source is one or more of diammonium phosphate, diammonium hydrogen phosphate and phosphoric acid; Further, the silicon source is one or both of silicon dioxide and silicic acid; Furthermore, the M source is one or more of oxides and salts.

[0017] Furthermore, the N source is one or more of oxides and salts.

[0018] Furthermore, the temperature of the first sintering is 600° C. to 900° C.; and the time of the first sintering is 4 to 12 hours.

[0019] Furthermore, the temperature of the second sintering is 600° C. to 900° C.; and the time of the second sintering is 4 to 12 hours.

[0020] Furthermore, the temperature of the third sintering is 600° C. to 900° C.; and the time of the second sintering is 4 to 12 hours.

[0021] Furthermore, it also includes: mixing the first modified sodium ion battery layered oxide positive electrode material with the metal oxide, and performing a fourth sintering to obtain the second modified sodium ion battery layered oxide positive electrode material.

[0022] Furthermore, the metal oxide is one or more of TiO2, Al2O3, ZrO2, MgO, CaO, ZnO, La2O3, Sc2O3, Y2O3, and Nb2O5.

[0023] Furthermore, the temperature of the fourth sintering is 500° C. to 700° C.; and the time of the fourth sintering is 4 to 12 hours.

[0024] Furthermore, the preparation method of the sodium ion battery layered oxide positive electrode material comprises: Wet-grinding a nickel source, an iron source, a manganese source, a sodium source, and a doping metal source to obtain a slurry; the doping metal source is one or more of Ca, Mg, Ti, Al, La, Nb, and Zr; The slurry is spray-dried to obtain a mixed powder; The mixed powder is sintered to obtain a layered oxide positive electrode material for a sodium ion battery.

[0025] In a third aspect, a sodium ion battery is provided, comprising the aforementioned modified sodium ion battery positive electrode material or the modified sodium ion battery positive electrode material prepared by the aforementioned preparation method.

[0026] Compared with the prior art, one or more of the above technical solutions can achieve at least one of the following beneficial effects: Provided is a modified sodium ion battery positive electrode material, comprising a sodium ion battery layered oxide positive electrode material and a Na y M x N 1-x(SiO4)2(PO4) layer, the battery assembled with the modified sodium ion battery positive electrode material has significantly improved discharge specific capacity, first coulomb efficiency and cycle performance, and the provided modified sodium ion battery positive electrode material can be widely used in the energy storage market.

[0027] By using some metal oxides as coating materials for further coating modification, the discharge specific capacity, first coulombic efficiency and cycle performance of the battery can be further improved.

[0028] The provided method for preparing the modified sodium ion battery positive electrode material has simple process, is easy to implement and has low cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0030] Figure 1 This is the XRD pattern of intermediate 2 prepared in step (1) of Example 1.

[0031] Figure 2 This is the SEM image of the modified sodium ion battery positive electrode material prepared in Example 1.

[0032] Figure 3 The cycle performance of button cells assembled with the sodium ion battery positive electrode materials prepared in Examples 1-2 and Comparative Examples 1-2. DETAILED DESCRIPTION

[0033] The present invention provides a modified sodium ion battery layered oxide positive electrode material, comprising a core and a first coating layer coated on at least a portion of the surface of the core, wherein the core is a sodium ion battery layered oxide positive electrode material, and the first coating layer is Na y M x N 1-x (SiO4)2(PO4), wherein M is one or more of Ti, Al, La, and Nb, N is one or more of Zr, Sc, and Y, x is 0.1 to 0.9, and y is 2.5 to 3.5; in the first coating layer, in the direction from the inner core to the surface, the concentration gradient of the M element content increases, and the concentration gradient of the N element content decreases.

[0034] Based on the O3-type sodium layered oxide core, a sodium fast ion conductor Na with a concentration gradient is formed on its surface. y M x N 1-xThe (SiO4)2(PO4) shell can maintain the structural stability of the inner core. The concentration gradient coating structure can precisely control and reduce the side reactions in the interface layer between the core and the shell. The gradient change can help the migration of sodium ions by regulating the proportion of metal ions. It has an ultra-high sodium ion diffusion coefficient, which is beneficial to the smooth deintercalation process of sodium ions in the inner core, and helps the migration of sodium ions in the interface layer between the positive electrode material and the electrolyte, thereby improving the electrical performance. The coating can also reduce the side reactions with the electrolyte and improve the electrochemical cycle stability of the material in the battery.

[0035] In some preferred embodiments, the chemical formula of the layered oxide positive electrode material for sodium ion batteries is Na a Ni b Fe c Mn d A e O2, wherein A is one or more of Ca, Mg, Ti, Al, La, Nb, and Zr, the value of a is 0.96~1.05, the value of b is 0.33~0.4, the value of c is 0.295~0.33, the value of d is 0.295~0.33, the value of e is 0~0.02, and b+c+d+e=1.

[0036] In some preferred embodiments, in the modified sodium ion battery layered oxide positive electrode material, the Na y M x N 1-x (SiO4)2(PO4) accounts for 1~2% of the molar amount of layered oxide positive electrode materials for sodium ion batteries.

[0037] In some preferred embodiments, in the direction from the core toward the surface, the first coating layer includes a first layer, a second layer and a third layer from the inside to the outside, and the first layer is Na y1 M x1 N 1-x1 (SiO4)2(PO4), the second layer is Na y2 M x2 N 1-x2 (SiO4)2(PO4), the third layer is Na y3 M x3 N 1-x3 (SiO4)2(PO4), where the value of x1 is 0.1~0.2, the value of y1 is 2.5~3.5, the value of x2 is 0.4~0.5, the value of y2 is 2.5~3.5, the value of x3 is 0.7~0.9, and the value of y3 is 2.5~3.5.

[0038] In some preferred embodiments, in the first coating layer, the molar weight of the first layer accounts for 20-35%, the molar weight of the second layer accounts for 30-40%, and the molar weight of the third layer accounts for 20-35%.

[0039] In some preferred embodiments, a second coating layer is also included, and the raw material of the second coating layer is a metal oxide (that is, the second coating layer is obtained by mixing and sintering the sodium ion battery layered oxide positive electrode material modified by coating the first coating layer and the raw material of the second coating layer), and the second coating layer is coated on at least part of the surface of the first coating layer. Further, by continuing to use metal oxides for coating modification, the metal oxide is easy to react with the sodium in the material to generate sodium transition metal oxides. On the one hand, the bonding force between the coating layer and the inner coating layer and the substrate is improved, and the stability of the coating layer is improved. On the other hand, a sodium ion conductor can be generated. The "island network effect" formed by the coating layer with a concentration gradient change can not only help the migration of sodium ions in the interface layer between the positive electrode material and the electrolyte, but also further reduce the occurrence of side reactions with the electrolyte, and improve the electrochemical cycle stability of the material in the battery.

[0040] In some preferred embodiments, the metal oxide is one or more of TiO2, Al2O3, ZrO2, MgO, CaO, ZnO, La2O3, Sc2O3, Y2O3, and Nb2O5, and is further preferably a nano-metal oxide.

[0041] In some preferred embodiments, the metal oxide is 0.05-0.15% of the molar amount of the layered oxide positive electrode material of the sodium ion battery.

[0042] The present invention also provides a method for preparing the aforementioned modified sodium ion battery layered oxide positive electrode material, comprising: S1, mixing a sodium ion battery layered oxide positive electrode material with a sodium source, an M source, a N source, a silicon source and a phosphorus source, and performing a first sintering to obtain an intermediate 1; S2, mixing the intermediate 1 with a sodium source, an M source, a N source, a silicon source and a phosphorus source, and performing a second sintering to obtain an intermediate 2; S3, mixing intermediate 2 with a sodium source, an M source, a N source, a silicon source and a phosphorus source, and performing a third sintering to obtain Na y M x N 1-xThe first modified sodium ion battery layered oxide positive electrode material is a (SiO4)2(PO4) coated modified sodium ion battery layered oxide positive electrode material; wherein M is one or more of Ti, Al, La, and Nb, N is one or more of Zr, Sc, and Y, x is 0.1 to 0.9, y is 2.5 to 3.5, and in the first modified sodium ion battery layered oxide positive electrode material, in the direction from the inner core to the surface, the concentration gradient of the M element content increases, and the N element content decreases from the concentration gradient.

[0043] In the above preparation method, based on the O3 type sodium layered oxide core, an in-situ sintering coating is performed on its surface to form a sodium fast ion conductor Na with a concentration gradient. y M x N 1-x The (SiO4)2(PO4) coating layer can utilize the residual sodium on the surface of the O3-type sodium-electrode layered oxide core to carry out Na y M x N 1-x The synthesis of the (SiO4)2(PO4) coating layer effectively reduces the residual sodium on the surface of the positive electrode material, which is beneficial to improve the processing performance and electrical properties of the material; at the same time, the sodium fast ion conductor Na with a concentration gradient is formed in situ on the surface of the core. y M x N 1-x The (SiO4)2(PO4) coating layer can maintain the structural stability of the inner core. The concentration gradient coating layer structure can precisely control and reduce the side reactions in the interface layer between the core and the shell. By regulating the proportion of metal ions and the gradient change, it helps the migration of sodium ions. It has an ultra-high sodium ion diffusion coefficient, which is beneficial to the smooth deintercalation process of sodium ions in the inner core, and can assist the migration of sodium ions in the interface layer between the positive electrode material and the electrolyte, and can also reduce the occurrence of side reactions with the electrolyte, thereby improving the cycle stability of the material.

[0044] In some preferred embodiments, in step S1, the M source, N source, silicon source and phosphorus source are in the order of Na y1 M x1 N 1-x1 (SiO4)2(PO4) ratio; In step S2, the M source, N source, silicon source and phosphorus source are in the order of Na y2 M x2 N 1-x2 (SiO4)2(PO4) ratio; In step S3, the M source, N source, silicon source and phosphorus source are in the order of Na y3 M x3 N 1-x3 (SiO4)2(PO4) ratio; In each step, the sodium source can be mixed according to a conventional ratio, for example, according to a ratio of 0.98 to 1.05 times the coefficient of Na in the chemical formula. For example, during the first sintering, the sodium source is mixed according to Na y1 M x1 N 1-x1 The Na coefficient y1 in (SiO4)2(PO4) is 0.98~1.05 times the ratio; Among them, the value of x1 is 0.1~0.2, the value of y1 is 2.5~3.5, the value of x2 is 0.4~0.5, the value of y2 is 2.5~3.5, the value of x3 is 0.7~0.9, and the value of y3 is 2.5~3.5.

[0045] In some embodiments, the sodium source is one or more of sodium carbonate, sodium hydroxide and sodium acetate.

[0046] In some embodiments, the phosphorus source is one or more of diammonium phosphate, diammonium hydrogen phosphate and phosphoric acid.

[0047] In some embodiments, the silicon source is one or both of silicon dioxide and silicic acid.

[0048] In some embodiments, the M source is one or more of an oxide and a salt. The salt may be a conventional salt in the art that can be thermally decomposed into an oxide, such as a nitrate, a carbonate, an acetate, and the like.

[0049] In some embodiments, the N source is one or more of oxides and salts. The salts may be conventional salts that can be thermally decomposed into oxides, such as nitrates, carbonates, acetates, and the like.

[0050] In some preferred embodiments, the temperature of the first sintering is 600° C. to 900° C.; and the time of the first sintering is 4 to 12 hours.

[0051] In some preferred embodiments, the temperature of the second sintering is 600° C. to 900° C.; and the time of the second sintering is 4 to 12 hours.

[0052] In some preferred embodiments, the temperature of the third sintering is 600° C. to 900° C.; and the time of the second sintering is 4 to 12 hours.

[0053] In some preferred embodiments, it also includes: mixing the first modified sodium ion battery layered oxide positive electrode material with the metal oxide, and performing a fourth sintering to obtain a second modified sodium ion battery layered oxide positive electrode material. Further, by continuing to use the metal oxide for coating modification, the metal oxide is easy to react with the sodium in the material to form a sodium transition metal oxide. On the one hand, the bonding force between the coating layer and the inner coating layer and the substrate is improved, and the stability of the coating layer is improved. On the other hand, a sodium ion conductor can be generated. The "island network effect" formed by the coating layer with a concentration gradient change can not only help the migration of sodium ions in the interface layer between the positive electrode material and the electrolyte, but also further reduce the occurrence of side reactions with the electrolyte, and improve the electrochemical cycle stability of the material in the battery.

[0054] In some preferred embodiments, the metal oxide is one or more of TiO2, Al2O3, ZrO2, MgO, CaO, ZnO, La2O3, Sc2O3, Y2O3, and Nb2O5.

[0055] In some preferred embodiments, the temperature of the fourth sintering is 500° C. to 700° C.; and the time of the fourth sintering is 4 to 12 hours.

[0056] The sodium ion battery layered oxide can be prepared by conventional preparation methods in the art, such as a solid phase method, a coprecipitation method, a spray drying method, and the like.

[0057] In some preferred embodiments, a sanding spray process is used, and various metal ion doping ratios are used to stabilize the core structure while reducing costs; the preparation method of the sodium ion battery layered oxide positive electrode material includes: Wet-grinding a nickel source, an iron source, a manganese source, a sodium source, and a doping metal source to obtain a slurry; the doping metal source is one or more of Ca, Mg, Ti, Al, La, Nb, and Zr; The slurry is spray-dried to obtain a mixed powder; The mixed powder is sintered to obtain a layered oxide positive electrode material for a sodium ion battery.

[0058] The sintering temperature is 900° C. to 1100° C., the sintering time is 6 to 24 hours, and the heating rate is 1 to 5° C. / min.

[0059] The solid content of the slurry obtained by the wet grinding is 20% to 40%.

[0060] The wet grinding can be achieved by using a sand mill; the sand milling method includes one of a disc type, a pin type, a turbine type and a dual-power type.

[0061] The particle size D50 of the slurry obtained by grinding is 0.5 μm <D50<3µm。

[0062] The nickel source may be one or more of nickel hydroxide, nickelous oxide, nickel oxide and nickel sulfate; the iron source may be one or more of iron oxide, iron hydroxide, iron chloride and iron sulfate; the manganese source may be one or more of manganese dioxide, manganese sulfate and manganese oxalate; the sodium source may be one or more of sodium carbonate, sodium hydroxide and sodium acetate.

[0063] The molar ratio of the sodium molar amount in the sodium source to the total metal molar amount in the nickel source, the iron source, the manganese source and the transition metal source is 0.95-1.05.

[0064] The spray drying can adopt conventional processes, and the spray drying method can be one of centrifugal, pressure and two-fluid. The process parameters of the spray drying can be conventionally controlled according to actual needs, for example, the inlet temperature is controlled to be 180°C to 280°C, and the outlet temperature is controlled to be 100°C to 130°C.

[0065] The present invention also provides a sodium ion battery, comprising the aforementioned modified sodium ion battery layered oxide positive electrode material or the modified sodium ion battery layered oxide positive electrode material prepared by the aforementioned preparation method.

[0066] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the specification, but the protection scope of the present invention is not limited to the following specific embodiments.

[0067] Example 1 (1) 3.3 mol NiO, 1.65 mol Fe2O3, 3.3 mol MnO2, 5 mol Na2CO3, 0.05 mol MgO, 0.05 mol TiO2 and a certain amount of deionized water were mixed with a solid content of 30% to obtain slurry 1; the obtained slurry 1 was ground in a turbine sand mill to obtain slurry 2, and the ground particle size D50 was 1 µm; the obtained slurry 2 was centrifugal spray dried with an inlet temperature of 230°C and an outlet temperature of 110°C to obtain intermediate 1; intermediate 1 was sintered in a box furnace with a sintering temperature of 1000°C, a heating rate of 5°C / min, and a sintering time of 24 h to obtain intermediate 2, whose XRD pattern is shown as follows: Figure 1 As shown, from Figure 1 It can be seen that the intermediate 2 obtained is an O3 phase sodium positive electrode material. Combined with the raw material ratio, it can be determined that the intermediate 2 obtained is an O3 phase sodium positive electrode material NaNi 0.33 Fe 0.33 Mn 0.33 Mg 0.005 Ti 0.005 O2; (2) The intermediate 2 was mixed with 0.05 mol Na2CO3, 0.005 mol La2O3, 0.023 mol ZrO2, 0.067 mol SiO2 and 0.033 mol H3PO4 and sintered at a temperature of 700°C, a heating rate of 5°C / min and a sintering time of 12 h to obtain the intermediate 3; The intermediate 3 obtained was mixed with 0.05 mol Na2CO3, 0.008 mol La2O3, 0.016 mol ZrO2, 0.067 mol SiO2 and 0.033 mol H3PO4 and sintered at a sintering temperature of 700°C, a heating rate of 5°C / min and a sintering time of 12 h to obtain the intermediate 4; The intermediate 4 was mixed with 0.05 mol Na2CO3, 0.012 mol La2O3, 0.01 mol ZrO2, 0.067 mol SiO2 and 0.033 mol H3PO4 and sintered at a temperature of 700°C, a heating rate of 5°C / min and a sintering time of 12 h to obtain the intermediate 5; (3) The intermediate 5 obtained was mixed with 0.01 mol of nano-Al2O3 and sintered at a sintering temperature of 600°C, a heating rate of 5°C / min, and a sintering time of 12 h to obtain the final modified sodium ion battery positive electrode material product. The SEM image of the prepared modified sodium ion battery positive electrode material is shown in Figure 2 shown.

[0068] Example 2 (1) 3.3 mol NiO, 1.65 mol Fe2O3, 3.3 mol MnO2, 5 mol Na2CO3, 0.05 mol MgO, 0.05 mol TiO2 and a certain amount of deionized water were mixed, with a solid content of 30%, to obtain slurry 1; the obtained slurry 1 was ground in a turbine sand mill to obtain slurry 2, and the ground particle size D50 was 1 µm; the obtained slurry 2 was centrifugal spray dried, with an inlet temperature of 230 ° C and an outlet temperature of 110 ° C. Intermediate 1 was obtained; intermediate 1 was sintered in a box furnace, with a sintering temperature of 1000 ° C, a heating rate of 5 ° C / min, and a sintering time of 24 h to obtain intermediate 2, which is an O3 phase sodium positive electrode material NaNi 0.33 Fe 0.33 Mn 0.33 Mg 0.005 Ti 0.005 O2; (2) The intermediate 2 was mixed with 0.05 mol Na2CO3, 0.005 mol La2O3, 0.023 mol ZrO2, 0.067 mol SiO2 and 0.033 mol H3PO4 and sintered at a temperature of 700°C, a heating rate of 5°C / min and a sintering time of 12 h to obtain the intermediate 3; The intermediate 3 obtained was mixed with 0.05 mol Na2CO3, 0.008 mol La2O3, 0.016 mol ZrO2, 0.067 mol SiO2 and 0.033 mol H3PO4 and sintered at a sintering temperature of 700°C, a heating rate of 5°C / min and a sintering time of 12 h to obtain the intermediate 4; The obtained intermediate 4 was mixed with 0.05 mol Na2CO3, 0.012 mol La2O3, 0.01 mol ZrO2, 0.067 mol SiO2 and 0.033 mol H3PO4 and sintered at a temperature of 700 °C, a heating rate of 5 °C / min and a sintering time of 12 h to obtain NaNi 0.33 Fe 0.33 Mn 0.33 Mg 0.005 Ti 0.005 O2@Na3La 0.3 Zr 0.7 (SiO4)2(PO4)@Na3La 0.5 Zr 0.5 (SiO4)2(PO4) @Na3La 0.7 Zr 0.3 (SiO4)2(PO4).

[0069] Comparative Example 1 3.3 mol NiO, 1.65 mol Fe2O3, 3.3 mol MnO2, 5 mol Na2CO3, 0.05 mol MgO, 0.05 mol TiO2 and a certain amount of deionized water were mixed with a solid content of 30% to obtain slurry 1; the obtained slurry 1 was ground in a turbine sand mill to obtain slurry 2, and the ground particle size D50 was 1 µm; the obtained slurry 2 was centrifugal spray dried with an inlet temperature of 230°C and an outlet temperature of 110°C. Obtain intermediate 1; sinter intermediate 1 in a box furnace at a sintering temperature of 1000°C, a heating rate of 5°C / min, and a sintering time of 24h to obtain intermediate 2; mix the obtained intermediate 2 with 0.15mol Na2CO3, 0.025mol La2O3, 0.05mol ZrO2, 0.20mol SiO2 and 0.1mol H3PO4 and sinter at a sintering temperature of 700°C, a heating rate of 5°C / min, and a sintering time of 12h to obtain the final product NaNi 0.33 Fe 0.33 Mn 0.33 Mg 0.005 Ti 0.005 O2@Na3La 0.5 Zr 0.5 (SiO4)2(PO4).

[0070] Comparative Example 2 3.3mol NiO, 1.65mol Fe2O3, 3.3mol MnO2, 5mol Na2CO3, 0.05mol MgO, 0.05mol TiO2 and a certain amount of deionized water were mixed, with a solid content of 30%, to obtain slurry 1; the obtained slurry 1 was ground in a turbine sand mill to obtain slurry 2, and the ground particle size D50 was 1µm; the obtained slurry 2 was centrifugal spray dried, with an inlet temperature of 230℃ and an outlet temperature of 110℃. Intermediate 1 was obtained; intermediate 1 was sintered in a box furnace, with a sintering temperature of 1000℃, a heating rate of 5℃ / min, and a sintering time of 24h to obtain NaNi 0.33 Fe 0.33 Mn 0.33 Mg 0.005 Ti 0.005 O2.

[0071] Example 3 The difference between this embodiment and embodiment 1 is that step (2) is different. Step (2) includes: (2) The intermediate 2 was mixed with 0.05 mol Na2CO3, 0.01 mol TiO2, 0.023 mol ZrO2, 0.067 mol SiO2 and 0.033 mol H3PO4 and sintered at a temperature of 700°C, a heating rate of 5°C / min and a sintering time of 12 h to obtain the intermediate 3; The intermediate 3 obtained was mixed with 0.05 mol Na2CO3, 0.016 mol TiO2, 0.016 mol ZrO2, 0.067 mol SiO2 and 0.033 mol H3PO4 and sintered at a sintering temperature of 700°C, a heating rate of 5°C / min and a sintering time of 12 h to obtain the intermediate 4; The obtained intermediate 4 was mixed with 0.05 mol Na2CO3, 0.024 mol TiO2, 0.01 mol ZrO2, 0.067 mol SiO2 and 0.033 mol H3PO4 and sintered at a sintering temperature of 700°C, a heating rate of 5°C / min and a sintering time of 12 h to obtain intermediate 5.

[0072] Example 4 The difference between this embodiment and embodiment 1 is that step (2) is different. Step (2) includes: (2) The intermediate 2 was mixed with 0.05 mol Na2CO3, 0.01 mol TiO2, 0.0115 mol Y2O3, 0.067 mol SiO2 and 0.033 mol H3PO4 and sintered at a temperature of 700°C, a heating rate of 5°C / min and a sintering time of 12 h to obtain the intermediate 3; The intermediate 3 obtained was mixed with 0.05 mol Na2CO3, 0.016 mol TiO2, 0.008 mol Y2O3, 0.067 mol SiO2 and 0.033 mol H3PO4 and sintered at a sintering temperature of 700°C, a heating rate of 5°C / min and a sintering time of 12 h to obtain the intermediate 4; The obtained intermediate 4 was mixed with 0.05 mol Na2CO3, 0.024 mol TiO2, 0.005 mol Y2O3, 0.067 mol SiO2 and 0.033 mol H3PO4 and sintered at a sintering temperature of 700°C, a heating rate of 5°C / min and a sintering time of 12 h to obtain intermediate 5.

[0073] Example 5 The difference between this embodiment and embodiment 1 is that step (2) is different. Step (2) includes: (2) The intermediate 2 was mixed with 0.075 mol Na2CO3, 0.0075 mol La2O3, 0.0345 mol ZrO2, 0.1005 mol SiO2 and 0.0495 mol H3PO4 and sintered at a temperature of 700°C, a heating rate of 5°C / min and a sintering time of 12 h to obtain the intermediate 3; The intermediate 3 obtained was mixed with 0.075 mol Na2CO3, 0.012 mol La2O3, 0.024 mol ZrO2, 0.1005 mol SiO2 and 0.0495 mol H3PO4 and sintered at a sintering temperature of 700°C, a heating rate of 5°C / min and a sintering time of 12 h to obtain the intermediate 4; The obtained intermediate 4 was mixed with 0.075 mol Na2CO3, 0.018 mol La2O3, 0.015 mol ZrO2, 0.1005 mol SiO2 and 0.0495 mol H3PO4 and sintered at a sintering temperature of 700°C, a heating rate of 5°C / min and a sintering time of 12 h to obtain intermediate 5.

[0074] Example 6 The difference between this embodiment and embodiment 1 is that step (2) is different. Step (2) includes: The intermediate 2 obtained was mixed with 0.05 mol Na2CO3, 0.005 mol La2O3, 0.023 mol ZrO2, 0.067 mol SiO2 and 0.033 mol H3PO4 and sintered at a sintering temperature of 750°C, a heating rate of 5°C / min and a sintering time of 12 h to obtain the intermediate 3; The intermediate 3 obtained was mixed with 0.05 mol Na2CO3, 0.008 mol La2O3, 0.016 mol ZrO2, 0.067 mol SiO2 and 0.033 mol H3PO4 and sintered at a temperature of 750°C, a heating rate of 5°C / min and a sintering time of 12 h to obtain the intermediate 4; The obtained intermediate 4 was mixed with 0.05 mol Na2CO3, 0.012 mol La2O3, 0.01 mol ZrO2, 0.067 mol SiO2 and 0.033 mol H3PO4 and sintered at a sintering temperature of 750°C, a heating rate of 5°C / min and a sintering time of 12 h to obtain intermediate 5.

[0075] Example 7 The difference between this embodiment and embodiment 1 is that step (2) is different. Step (2) includes: The intermediate 2 obtained was mixed with 0.05 mol Na2CO3, 0.005 mol La2O3, 0.023 mol ZrO2, 0.067 mol SiO2 and 0.033 mol H3PO4 and sintered at a temperature of 650°C, a heating rate of 5°C / min and a sintering time of 12 h to obtain the intermediate 3; The intermediate 3 obtained was mixed with 0.05 mol Na2CO3, 0.008 mol La2O3, 0.016 mol ZrO2, 0.067 mol SiO2 and 0.033 mol H3PO4 and sintered at a temperature of 650°C, a heating rate of 5°C / min and a sintering time of 12 h to obtain the intermediate 4; The obtained intermediate 4 was mixed with 0.05 mol Na2CO3, 0.012 mol La2O3, 0.01 mol ZrO2, 0.067 mol SiO2 and 0.033 mol H3PO4 and sintered at a sintering temperature of 650°C, a heating rate of 5°C / min and a sintering time of 12 h to obtain intermediate 5.

[0076] Example 8 The only difference between this embodiment and embodiment 1 is that the amount of nano-Al2O3 used in step (3) is different, and the amount of nano-Al2O3 used is 0.015 mol.

[0077] Example 9 The only difference between this embodiment and embodiment 1 is that the amount of nano-Al2O3 used in step (3) is different, and the amount of nano-Al2O3 used is 0.005 mol.

[0078] Example 10 The only difference between this embodiment and embodiment 1 is that nano-La2O3 is used instead of nano-Al2O3 in step (3).

[0079] Embodiment 11 The only difference between this embodiment and embodiment 1 is that nano-MgO is used instead of nano-Al2O3 in step (3).

[0080] Example 12 The difference between this embodiment and embodiment 1 is that step (2) is different. Step (2) includes: (2) The intermediate 2 was mixed with 0.0375 mol Na2CO3, 0.00375 mol La2O3, 0.01725 mol ZrO2, 0.05025 mol SiO2 and 0.02475 mol H3PO4 and sintered at a temperature of 700°C, a heating rate of 5°C / min and a sintering time of 12 h to obtain the intermediate 3; The intermediate 3 obtained was mixed with 0.075 mol Na2CO3, 0.012 mol La2O3, 0.024 mol ZrO2, 0.1005 mol SiO2 and 0.0495 mol H3PO4 and sintered at a sintering temperature of 700°C, a heating rate of 5°C / min and a sintering time of 12 h to obtain the intermediate 4; The obtained intermediate 4 was mixed with 0.0375 mol Na2CO3, 0.009 mol La2O3, 0.0075 mol ZrO2, 0.05025 mol SiO2 and 0.02475 mol H3PO4 and sintered at a sintering temperature of 700°C, a heating rate of 5°C / min and a sintering time of 12 h to obtain intermediate 5.

[0081] The positive electrode materials prepared in Examples 1 to 12 and Comparative Examples 1 to 2 were subjected to battery assembly and electrochemical performance testing according to the following method: The positive electrode material is used as the active material. The mass ratio of active material: conductive agent (Super P): binder (PVDF) is 90:5:5. An appropriate amount of solvent NMP is added to adjust the solid content. After being stirred into slurry by a pulping machine, it is coated on aluminum foil. After coating, the electrode is dried in an oven at 110°C for 4 hours. Sodium sheet is used as the negative electrode, glass fiber is used as the diaphragm, and 1M NaPF6 (solvent EC:DEC=1:1 Vol%) is used as the electrolyte. The button cell is assembled in a glove box. The battery is tested at 25°C in the voltage range of 2.0-4.15V. After two cycles of activation at 0.1C, one cycle of testing the rate performance at 0.2C and 0.5C, a 50-cycle cycle performance test at 1C is performed.

[0082] The cycle performance of the batteries assembled in Examples 1-2 and Comparative Examples 1-2 is shown in the figure below: Figure 3 The electrical properties of the batteries assembled in Examples 1 to 12 and Comparative Examples 1 to 2 are shown in Table 1.

[0083] As can be seen from Table 1, compared with the battery assembled in Example 2, the battery assembled in Example 1 is first coated with the gradient coating layer Na y M x N 1-x Compared with the battery assembled with the sodium ion battery positive electrode material of (SiO4)2(PO4) coated with alumina layer, the battery with only gradient coating layer Na y M x N 1-xFor the battery assembled with the sodium ion battery positive electrode material of (SiO4)2(PO4), the discharge specific capacity, the first coulombic efficiency and the cycle performance at 1C are improved. After analysis, the improvement of the discharge specific capacity and the first coulombic efficiency may be because in Example 1, alumina reacts with the intermediate 5 to generate sodium aluminate, and sodium aluminate is a fast ion conductor, which promotes ion conduction, thereby effectively improving the discharge specific capacity.

[0084] It can be seen from Table 1 that the uniform concentration coating layer Na prepared in Comparative Example 1 y M x N 1-x Compared with the battery assembled with the sodium ion battery positive electrode material coated with (SiO4)2(PO4), the concentration gradient coating layer Na y M x N 1-x The initial charge and discharge capacity, coulombic efficiency and cycle performance of batteries assembled with (SiO4)2(PO4) coated sodium ion battery positive electrode materials have been significantly improved. After analysis, it was found that the concentration gradient coating layer structure can accurately control and reduce the occurrence of side reactions in the interface layer between the core and shell. By regulating the proportion of metal ions and the gradient change, it helps the migration of sodium ions and improves the stability of the material.

[0085] It can be seen from Table 1 that compared with the battery assembled with the uncoated sodium ion battery positive electrode material prepared in Comparative Example 2, the uniform concentration coating layer Na prepared in Comparative Example 1 y M x N 1-x (SiO4)2(PO4) coated sodium ion battery positive electrode material, concentration gradient coating layer Na prepared in Example 2 y M x N 1-x The performance of the batteries assembled with (SiO4)2(PO4) coated sodium ion battery cathode materials was improved, which fully demonstrated that Na y M x N 1-x (SiO4)2(PO4) coating modification produced an effect.

[0086] It can also be seen from Table 1 that, under the conditions of changing the type and amount of coating layer materials, as well as process parameters, the battery performance assembled from the modified sodium ion battery positive electrode materials prepared in different embodiments has certain differences, but in general, the first capacity is relatively high and the cycle performance is relatively good.

[0087] In summary, the present invention forms a transition metal ion-doped O3 type sodium layered oxide as the core by sintering nickel iron manganese oxide under a sand mill spray process, and uses a low-cost oxide for synthesis, but the O3 type sodium layered oxide has poor cycle performance and a high residual sodium content. Therefore, on the basis of the O3 type sodium layered oxide core, multiple in-situ sintering is performed on its surface to form a mesh sodium fast ion conductor Na with a concentration gradient. y M x N 1-x (SiO4)2(PO4) and metal oxide shells can utilize the residual sodium on the surface of the O3-type sodium layered oxide core to carry out Na y M x N 1-x The synthesis of the (SiO4)2(PO4) coating layer can effectively reduce the residual sodium on the surface, which is beneficial to the processing performance and electrical properties of the material; at the same time, the sodium fast ion conductor Na with a concentration gradient formed in situ on the surface of the core y M x N 1-x The (SiO4)2(PO4) coating layer can maintain the structural stability of the inner core. The coating layer structure with a concentration gradient can precisely control and reduce the side reactions at the interface layer between the core and the shell. By regulating the proportion of metal ions and the gradient change, it helps the migration of sodium ions. It has an ultra-high sodium ion diffusion coefficient, which is beneficial to the smooth deintercalation of sodium ions in the inner core. In addition, the "island network effect" formed by the outer layer with a concentration gradient change and the metal oxide coating can not only assist the migration of sodium ions at the interface layer between the positive electrode material and the electrolyte, but also reduce the occurrence of side reactions with the electrolyte, thereby improving the cycle stability of the material.

[0088] Table 1 Comparison data of power-off test The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A modified sodium ion battery positive electrode material, characterized in that: The invention comprises a core and a first coating layer coated on at least a part of the surface of the core, wherein the core is a layered oxide positive electrode material for a sodium ion battery, and the first coating layer is Na y M x N 1-x (SiO4)2(PO4), wherein M is one or more of Ti, Al, La, and Nb, N is one or more of Zr, Sc, and Y, x is 0.1 to 0.9, and y is 2.5 to 3.5; in the first coating layer, in the direction from the core to the surface, the concentration gradient of the M element content increases, and the concentration gradient of the N element content decreases.

2. The modified sodium ion battery positive electrode material according to claim 1, characterized in that The layered oxide positive electrode material for sodium ion battery is an O3 type sodium ion battery positive electrode material; the chemical formula of the O3 type sodium ion battery positive electrode material is Na a Ni b Fe c Mn d A e O2, wherein A is one or more of Ca, Mg, Ti, Al, La, Nb, and Zr, a is 0.96 to 1.05, b is 0.33 to 0.4, c is 0.295 to 0.33, d is 0.295 to 0.33, e is 0 to 0.02, and b+c+d+e=1; In the modified sodium ion battery positive electrode material, the Na y M x N 1-x (SiO4)2(PO4) is 1-2% of the molar amount of layered oxide cathode materials for sodium ion batteries; The first coating layer includes a first layer, a second layer and a third layer in the direction from the core to the surface, and the first layer is Na y1 M x1 N 1-x1 (SiO4)2(PO4), the second layer is Na y2 M x2 N 1-x2 (SiO4)2(PO4), the third layer is Na y3 M x3 N 1-x3 (SiO4)2(PO4), where x1 is 0.1~0.2, y1 is 2.5~3.5, x2 is 0.4~0.5, y2 is 2.5~3.5, x3 is 0.7~0.9, y3 is 2.5~3.5; In the first coating layer, the molar weight of the first layer accounts for 20-35%, the molar weight of the second layer accounts for 30-40%, and the molar weight of the third layer accounts for 20-35%.

3. The modified sodium ion battery positive electrode material according to claim 1, characterized in that It also includes a second coating layer, the raw material of the second coating layer is a metal oxide, and the second coating layer is coated on at least a part of the surface of the first coating layer; The metal oxide is one or more of TiO2, Al2O3, ZrO2, MgO, CaO, ZnO, La2O3, Sc2O3, Y2O3, and Nb2O5; The metal oxide is 0.05-0.15% of the molar amount of the layered oxide positive electrode material of the sodium ion battery.

4. The method for preparing a modified sodium ion battery positive electrode material according to any one of claims 1 to 3, characterized in that: include: S1, mixing a sodium ion battery layered oxide positive electrode material with a sodium source, an M source, a N source, a silicon source and a phosphorus source, and performing a first sintering to obtain an intermediate 1; S2, mixing the intermediate 1 with a sodium source, an M source, a N source, a silicon source and a phosphorus source, and performing a second sintering to obtain an intermediate 2; S3, mixing intermediate 2 with a sodium source, an M source, a N source, a silicon source and a phosphorus source, and performing a third sintering to obtain Na y M x N 1-x The first modified sodium ion battery layered oxide positive electrode material is a (SiO4)2(PO4) coated modified sodium ion battery layered oxide positive electrode material; wherein M is one or more of Ti, Al, La, and Nb, N is one or more of Zr, Sc, and Y, x is 0.1 to 0.9, y is 2.5 to 3.5, and in the first modified sodium ion battery layered oxide positive electrode material, in the direction from the inner core to the surface, the concentration gradient of the M element content increases, and the N element content decreases from the concentration gradient.

5. The method for preparing the modified sodium ion battery positive electrode material according to claim 4, characterized in that: In step S1, the M source, N source, silicon source and phosphorus source are in the order of Na y1 M x1 N 1-x1 (SiO4)2(PO4) ratio; In step S2, the M source, N source, silicon source and phosphorus source are in the order of Na y2 M x2 N 1-x2 (SiO4)2(PO4) ratio; In step S3, the M source, N source, silicon source and phosphorus source are in the order of Na y3 M x3 N 1-x3 (SiO4)2(PO4) ratio; Among them, the value of x1 is 0.1~0.2, the value of y1 is 2.5~3.5, the value of x2 is 0.4~0.5, the value of y2 is 2.5~3.5, the value of x3 is 0.7~0.9, and the value of y3 is 2.5~3.

5.

6. The method for preparing the modified sodium ion battery positive electrode material according to claim 4, characterized in that: The sodium source is one or more of sodium carbonate, sodium hydroxide and sodium acetate; The phosphorus source is one or more of diammonium phosphate, diammonium hydrogen phosphate and phosphoric acid; The silicon source is one or both of silicon dioxide and silicic acid; The M source is one or more of oxides and salts; The N source is one or more of oxides and salts.

7. The method for preparing the modified sodium ion battery positive electrode material according to claim 4, characterized in that: The first sintering temperature is 600° C. to 900° C.; the first sintering time is 4 to 12 hours; The temperature of the second sintering is 600°C to 900°C; the time of the second sintering is 4 to 12 hours; The temperature of the third sintering is 600° C. to 900° C.; the time of the third sintering is 4 to 12 hours.

8. The method for preparing the modified sodium ion battery positive electrode material according to claim 4, characterized in that: Also includes: Mixing the first modified sodium ion battery layered oxide positive electrode material and the metal oxide, and performing a fourth sintering to obtain a second modified sodium ion battery layered oxide positive electrode material; Preferably, the metal oxide is one or more of TiO2, Al2O3, ZrO2, MgO, CaO, ZnO, La2O3, Sc2O3, Y2O3, and Nb2O5; Preferably, the temperature of the fourth sintering is 500° C. to 700° C.; and the time of the fourth sintering is 4 to 12 hours.

9. The method for preparing the modified sodium ion battery positive electrode material according to claim 4, characterized in that: The preparation method of the sodium ion battery layered oxide positive electrode material comprises: Wet-grinding a nickel source, an iron source, a manganese source, a sodium source, and a doping metal source to obtain a slurry; the doping metal source is one or more of Ca, Mg, Ti, Al, La, Nb, and Zr; The slurry is spray-dried to obtain a mixed powder; The mixed powder is sintered to obtain a layered oxide positive electrode material for a sodium ion battery.

10. A sodium ion battery, characterized in that It includes the modified sodium ion battery positive electrode material as described in any one of claims 1 to 3 or the modified sodium ion battery positive electrode material prepared by the preparation method as described in any one of claims 4 to 9.